2008
DOI: 10.1007/s00702-008-0159-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct subcellular localization of BDNF transcripts in cultured hypothalamic neurons and modification by neuronal activation

Abstract: We investigated subcellular localization of total brain-derived neurotrophic factor (BDNF) mRNA (panBDNF) and its different 5' exon-specific transcripts in cultured hypothalamic neurons. Non-isotopic in situ hybridization (DIG-labeled exon-specific riboprobes) associated with immunocytochemical MAP2 or GFAP labeling was used for detection. We found that under basal conditions panBDNF mRNA was localized in neuronal soma and in primary dendritic processes. Transcripts I and II were weakly expressed in neuronal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 50 publications
3
15
0
1
Order By: Relevance
“…A similar segregation of BDNF mRNA variants has also been observed in hypothalamic (25) and cortical neurons (15), suggesting that our model can be applied to several neuronal types. A slight discrepancy in the actual distances or RDF values between this and our previous studies (15,17) does not affect the general conclusions on the differential localization of BDNF transcripts, and is accounted for by different culture conditions and by the fact that only apical dendrites were measured here, whereas previous studies also included basal dendrites, which are generally shorter and tend to have a higher RDF.…”
Section: Discussionsupporting
confidence: 75%
“…A similar segregation of BDNF mRNA variants has also been observed in hypothalamic (25) and cortical neurons (15), suggesting that our model can be applied to several neuronal types. A slight discrepancy in the actual distances or RDF values between this and our previous studies (15,17) does not affect the general conclusions on the differential localization of BDNF transcripts, and is accounted for by different culture conditions and by the fact that only apical dendrites were measured here, whereas previous studies also included basal dendrites, which are generally shorter and tend to have a higher RDF.…”
Section: Discussionsupporting
confidence: 75%
“…For instance, the mood stabilizers lithium and valproate selectively activate promoter 6 of BDNF (Yasuda et al, 2009), while chronic duloxetine treatment induces enhanced mRNA levels for exons 1 and 4; however, the expression of exon 6 was reduced in the cortex (Calabrese et al, 2007). In our study, the treatments considered caused an increase in BDNF transcription and a specific translocation in CA3 distal dendrites of the exon 6 BDNF mRNA isoform, while in the case of exon 4, which was previously found in the soma and proximal dendrites (Aliaga et al, 2009;Baj et al, 2011), we found proximal or no dendritic staining and a decrease in CA3 following RBX treatment. Hence, these results are further evidence that enhanced BDNF mRNA translocation in distal dendrites is not a direct consequence of increased global transcription (Tongiorgi, 2008).…”
Section: Discussionsupporting
confidence: 45%
“…The studies mentioned above quantified total BDNF expression. However, transcripts initiating from exons I, II and III are expressed predominantly in neurons whereas transcripts initiating from exons IV, V and VI are expressed by both neurons and astrocytes within the naïve brain [69]. Normal expression of all transcripts may be necessary for wellness, as a knockout of even one of the 9 BDNF transcripts caused depressive-like behavior of mice [70].…”
Section: Discussionmentioning
confidence: 99%